Konsep Dasar Mutu: Integrasi Nilai Spiritual, Manajerial, dan Profesional dalam Peningkatan Kualitas Pendidikan - Abu Muhlis; Nur Fika Anjani; Mua’limin, Mua’limin (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
This article discusses the basic concepts of education quality as an effort to comprehensively understand how quality principles are applied in various educational contexts, both general and religious. This study focuses on a conceptual analysis of the meaning, principles, and strategies for improving education quality based on relevant literature. This study uses a qualitative approach with a literature review method involving analysis of 26 scientific articles published between 2020 and 2025. These articles were obtained through Google Scholar and Publish or Perish using the keywords “education quality management,” “basic concepts of quality,” and “school quality improvement.” After screening and selection, five main articles were analyzed in depth to identify themes and interrelationships between concepts. The results of the study show that the concept of quality covers aspects of planning, implementation, supervision, and evaluation that are oriented towards the satisfaction of education customers—namely students, parents, and the community. The Total Quality Management (Hasnadi, 2021) and School-Based Management (Junindra et al., 2022) approaches have proven to be effective in creating a sustainable culture of quality. In addition, the integration of spiritual values and Kaizen principles (Latif & Sesmiarni, 2024; Zulkarnain, 2023) enriches the ethical dimension of educational quality management.